2018
DOI: 10.1111/jocn.14610
|View full text |Cite
|
Sign up to set email alerts
|

In their shoes: An ontological perspective on empathy in nursing practice

Abstract: Aims and objectives To present an enquiry into empathy as part of nursing ontology. The work aims to improve understanding of how empathy is developed and used in practice. Background Empathy is the ability to grasp the frame of reference of another. As such, empathy is a key feature of nursing practice involving self‐awareness and the use of emotion in interpersonal understanding. Method As part of a larger study into the commonality of emotion in nursing, thirty‐three nurses across a range of settings talked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 37 publications
(128 reference statements)
1
43
0
Order By: Relevance
“…Linking to this, there is great interest in elucidating the role of socially relevant variables that can modulate the relations between the maintenance of social interactions and PWB. Thus, it has been suggested that empathy, as a core psychological disposition mechanism could directly or indirectly affect interpersonal relationships in nursing work settings .…”
Section: Introductionmentioning
confidence: 99%
“…Linking to this, there is great interest in elucidating the role of socially relevant variables that can modulate the relations between the maintenance of social interactions and PWB. Thus, it has been suggested that empathy, as a core psychological disposition mechanism could directly or indirectly affect interpersonal relationships in nursing work settings .…”
Section: Introductionmentioning
confidence: 99%
“…Seven of the papers included in this review discussed the importance of empathic imagination. For example, Ozcan et al (, p. 135) referred to nursing students' ability to imagine themselves in another person's place and to look at events from that person's point of view; and McKinnon (, p. 3891) found that empathy requires the ability to imagine and represent the imagined perception within the self. Two papers (Cliffordson, ; Latimer et al, ) also included the notion of “fantasy,” one of the subscales of the Interpersonal Reactivity Index (IRI) (Davis, , p. 119), and described as the tendency to imaginatively transpose oneself into fictional situations or to identify with fictional characters.…”
Section: Resultsmentioning
confidence: 99%
“…The majority (n = 6) were literature reviews (Campbell-Yeo, Latimer, & Johnston, 2008;Dinkins, 2018;Hunt, Denieffe, & Gooney, 2017;Irving & Dickson, 2004;Kunyk & Olson, 2001;Määttä, 2006). Three were quasi-experimental exploratory singlegroup or two-group studies using quantitative measures and reporting findings from primary research such as surveys of students or nurses from different clinical backgrounds (Cliffordson, 2002;Latimer et al, 2017;Marcysiak, Dabrowska, & Marcysiak, 2014), and two were qualitative studies using interview, or interview and observation (McKinnon, 2018;Wiseman, 2007). The studies were conducted by authors from Canada (n = 4), UK (n = 3), Sweden (n = 2), Poland (n = 1) and USA (n = 1).…”
Section: Conceptual Studiesmentioning
confidence: 99%
See 2 more Smart Citations